The impact of illegal gold mining on the environment in Kwekwe district - Muraza, Taonga Agrippa (Midlands State University, 2017)
The main scope of the research was to establish the major environmental challenges caused by gold panning in Kwekwe district in Midlands Province of Zimbabwe. In this study the qualitative with a combination of minor aspects quantitative research paradigms were used with a sample drawn from panners, and stakeholders. The stakeholders comprised local government officials, Environmental Management Authorities and officials drawn from local mining organisations also the local people dwelling along the Munyati Sebakwe and Kwekwe river banks. Given the gravity of the study, purposive sampling techniques were used with extreme variations in selecting panners and other stakeholders while at the same time maintaining a gender balance to the respondents. Purposive sampling was very useful to this research, this so basing on the fact that the researcher could select unique cases that were especially informative. The mainly base on qualitative quantitative data which was collected through the use of face to face interviews and a combination of and observations managed provide an in built triangulation for the study .The study established that gold mining activities which are poverty driven , have incalculably contributed to environmental damages such as deforestation, soil erosion, siltation , and the destruction of aquatic based food chains as a result of disposal of waste material and the use of chemicals such as mercury an d cyanide . Gold panning have been seen as having resulted in a serious health hazards associated with the lack of proper hygiene standards in the squatter camps.